(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2016)
Dwelling Riparian is not an archaeological artifacts or ruins of civilization, but the physical figure of communities that are still alive and live. Socially, the Musi River not merely as a means of transport and make a living alone. Moreover Musi River Palembang form of existence of cultural sovereignty. Riverside settlements are not only inherent elegance spatial pattern alone, but also contains exemplary values, philosophy, and belief in the primordial Palembang riverside cultural background and meaning of culture. The goals of this study are, 1) to observe the evolution processes of dwelling culture and to compare the traditional spatial forms and the transformed ones. 2) to emphasize the former attitude and to propose a sustainable strategy for developing the dwelling type by respecting and adopting the traditional culture and historic apologue. The concrete tactics for construction and architectural concepts are proposed in this paper.